Germination, physio-anatomical behavior, and productivity of wheat plants irrigated with magnetically treated seawater - Selim, Dalia Abdel-Fattah H.; Zayed, Muhammad; Ali, Maha M. E.; Eldesouky, Heba S.; Bonfill, Mercedes; El-Tahan, Amira M.; Ibrahim, Omar M.; El-Saadony, Mohamed T.; El-Tarabily, Khaled A.; AbuQamar, Synan F.; Elokkiah, Samira (Frontiers in Plant Science, 2022)
Salinity is an abiotic stress that reduces the seed germination and productivity of wheat. The objective of this study was to assess the impact of irrigation with magnetically treated seawater on the germination, growth, certain physiological and anatomical parameters, and production attributes of wheat (Triticum aestivum L.) cv. Sakha 93 plants. Experiments were conducted in the Experimental Farm of the Faculty of Agriculture, Menoufia University, Egypt, during two consecutive winter seasons. Pot experiments involved ten treatments with non-magnetized and magnetized water with various degrees of salinity. Plant samples were taken 95 days after sowing. Irrigation with magnetically treated seawater was found to have beneficial effects on plant growth, water relations, biochemical characteristics, and yield components compared with untreated plants. The germination of wheat seeds increased 13% when treated with magnetic seawater. On the yield scale, the spike length was increased by 40% in season one, and 82% in season two when compared to the control, while the weight of 100 grains increased by 148% and 171%, in each season, respectively, when treated with magnetic water. The anatomical leaf and stem parameters of the plants were markedly improved by watering with magnetically treated seawater at 10 dS.m-1 compared to the control. However, the leaf water deficit, transpiration rate, and abscisic acid content in the plant shoots decreased significantly (P<0.05). The use of magnetically treated seawater of up to 7.5 dS.m-1, instead of tap water, is recommended due to benefits to germination and seedling parameters, growth, yield, and physiological, chemical, and anatomical characteristics. In conclusion, magnetic treatment of seawater improved germination performance, growth and yield of wheat under saline conditions.